2018
DOI: 10.1371/journal.pone.0200299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term, sublethal fipronil and its metabolite on dragonfly feeding activity

Abstract: Dragonflies, Sympetrum spp., are indispensable to agriculture and are a central element of culture in Japan. However, S. frequens populations in rice paddy fields have declined in recent decades. Dragonfly larvae are predatory aquatic insects that feed on other organisms found in habitats with slow-moving or standing water. The increasing use of fipronil and neonicotinoid insecticides in agriculture is also increasing exposure to Sympetrum spp. in larval stages through paddy soil and water. The role of fiproni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 70 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…Such delays in larval development due to feeding inhibition may result in impaired larval development and unsuccessful emergence of adults. The high value of FI percentage, calculated in this study proves that C. procera latex possess feeding inhibition properties as, generally, the higher the value of FI, the lower the rate of feeding (Szczepanik et al, 2016 andJinguji et al, 2018). The feeding inhibition of C. procera leave extract against another two lepidopteran larvae; Spodoptera littoralis and Spodoptera lithura has been reported by Abdel-Rahman and Al-Mozini (2007) and Bakavathiappan, et al (2012), respectively.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Such delays in larval development due to feeding inhibition may result in impaired larval development and unsuccessful emergence of adults. The high value of FI percentage, calculated in this study proves that C. procera latex possess feeding inhibition properties as, generally, the higher the value of FI, the lower the rate of feeding (Szczepanik et al, 2016 andJinguji et al, 2018). The feeding inhibition of C. procera leave extract against another two lepidopteran larvae; Spodoptera littoralis and Spodoptera lithura has been reported by Abdel-Rahman and Al-Mozini (2007) and Bakavathiappan, et al (2012), respectively.…”
Section: Discussionsupporting
confidence: 75%
“…This experiment was continued until adult emergence from pupae in control group, then accumulated mortality, duration of larval stage, pupal weight and the consumed diet weights were calculated. The feeding inhibition percentage and feeding indices were estimated after 15 days of feeding using the following formulae (Waldbauer, 1968 andJinguji et al, 2018):…”
Section: Toxicity Bioassaymentioning
confidence: 99%
“…During acute intoxication, structure–function studies and resistant insect strains have demonstrated that RDL is the main target (Ffrench‐Constant et al, 1993; Hosie, Baylis, Buckingham, & Sattelle, 1995). However, in the case of off‐target species, the mechanism underlying death from chronic sublethal exposure has been less investigated (Aliouane et al, 2009; Charreton et al, 2015; Decourtye et al, 2005; El Hassani, Dacher, Gauthier, & Armengaud, 2005; Jinguji, Ohtsu, Ueda, & Goka, 2018; Pisa et al, 2015). In particular, there is a lack of the comparative analysis of the different GABA receptor properties needed to identify all the molecular determinants that could be involved.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus. The oviposition repellent effect of the NaCl concentration was estimated using an oviposition inhibition (OI) score, which was calculated using the following equation and in accordance with inhibition test methods for testing chemicals (Jinguji et al 2018):…”
mentioning
confidence: 99%